Analisis Pengaruh Likuiditas, Solvabilitas, dan Profitabilitas terhadap Market Value Added (MVA) - Aisyana, Marsya; Sun, Yen (Bina Nusantara University, 2012)
This study aims for analyzing the influence of liquidity, solvability and profitability to market value added. There are 22 companies of LQ 45 used as samples during the period of 2007-2009. Sampling technique used in this study is purposive sampling. Furthermore, the statistical test used in the data analysis and hypothesis testing is multiple linear regressions. The independent variable consists of 6 variables; acid-test ratio, debt ratio, debt to equity ratio, times interest earned (TIE), return on asset (ROA) dan return on equity (ROE). While the dependent variable used is market value added (MVA). The result shows that only return on asset (ROA) has a significant and positive impact to market value added (MVA). Whereas, the acid-test ratio and debt ratio has a positive and insignificant effect, the debt to equity ratio, times interest earned (TIE), and return on equity (ROE) has a negative and insignificant effect to market value added (MVA).